CONTENT OF PARENT AND NEIGHBORHOOD COOPERATION IN PRIMARY SCHOOL EDUCATION LESSON (Academicia Globe: Inderscience Research, 2023)
This article provides information on the content of parental and Neighborhood Cooperation in the primary school education lesson.